DemoWiz: re-performing software demonstrations for a live presentation - Chi, Pei-Yu; Lee, Bongshin; Drucker, Steven (Proceedings of the 32nd annual ACM conference on Human factors in computing systems, 2014)
Showing a live software demonstration during a talk can be engaging, but it is often not easy: presenters may struggle with (or worry about) unexpected software crashes and encounter issues such as mismatched screen resolutions or faulty network connectivity. Furthermore, it can be difficult to recall the steps to show while talking and operating the system all at the same time. An alternative is to present with pre-recorded screencast videos. It is, however, challenging to precisely match the narration to the video when using existing video players. We introduce DemoWiz, a video presentation system that provides an increased awareness of upcoming actions through glanceable visualizations. DemoWiz supports better control of timing by overlaying visual cues and enabling lightweight editing. A user study shows that our design significantly improves the presenters’ perceived ease of narration and timing compared to a system without visualizations that was similar to a standard playback control. Furthermore, nine (out of ten) participants preferred DemoWiz over the standard playback control with the last expressing no preference.